4 '-Aminochalcones As Novel Inhibitors of the Chlorinating Activity of Myeloperoxidase - Zeraik, M. L. [UNESP]; Ximenes, V. F. [UNESP]; Regasini, L. O. [UNESP]; Dutra, L. A. [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Fonseca, L. M. [UNESP]; Coelho, D.; Machado, S. A. S.; Bolzani, Vanderlan da Silva [UNESP] (Bentham Science Publ Ltd, 2012)
The excessive activation of neutrophils generates reactive oxygen species (ROS) and the secretion of primary granular enzymes, such as myeloperoxidase (MPO), which is implicated in numerous inflammatory diseases. The aim of this study was to evaluate chalcones as inhibitors of the chlorinating activity of MPO using in vitro and ex vivo assays. In addition to cytotoxic properties, the inhibition of respiratory burst, the scavenger capacity, and the oxidation potential were measured. 4'-Aminochalcone (1), 4'-amino-4-fluorochalcone (2), and 4'-amino-4-methylchalcone (3) exhibited potent inhibition of the chlorinating activity of MPO, as evaluated in a neutrophil system and a free cell system, to the following degree: (1) IC50 = 0.265 +/- 0.036 mu ol L-1; (2) IC50 = 0.250 +/- 0.081 mu ol L-1; and (3) IC50 = 0.250 +/- 0.012 mu ol L-1. These values were similar to those for 5-fluorotryptamine (IC50 = 0.192 +/- 0.012 mu ol L-1), a compound considered to be a potent MPO inhibitor. These aminochalcones were not toxic to neutrophils at concentrations below 100 mu ol L-1, as determined by the trypan blue exclusion assay. Compounds 1-3 presented a high oxidation potential (E-pa1 approximate to 0.80 V), low scavenger capacity against DPPH center dot and HOCl, and low inhibition of respiratory burst. These data indicated that aminochalcones are potent inhibitors of MPO chlorinating activity, a new property for chalcone derivatives, given that they are neither antioxidant agents nor inhibitors of respiratory burst. In conclusion, the selected aminochalcones have potential as pharmacological agents for inflammatory diseases.
Keywords: Anti-inflammatory; antioxidant; chalcones; hypochlorous acid; myeloperoxidase inhibition; neutrophils; aminochalcones; reactive oxygen species; redox potential; scavenger capacity